Kemampuan Koneksi Matematis Peserta didik pada Pembelajaran Bangun Ruang dengan Strategi REACT Kelas VIII.A MTs Pancasila Kota Bengkulu - Merlina Eka Putri; Mela Aziza (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
One of the objectives of mathematics learning is to improve the mathematical connection abilities on students. However, our observations showed that the mathematical connection abilities on students at MTs Pancasila, Bengkulu was still poor. This encourages the need for a learning strategy which is able to direct students to connect with what they have learned into everyday lives. Therefore, this study aimed to examine students’ ability in understanding mathematical concepts to solve problems related to cubes and rectangular prism topic. This was qualitative study with the REACT strategy. Cubes and rectangular prism was one of the mathematics topics of the basic competencies which have to be mastered by students in grade VIII. The subjects were 20 students who took the test and seven students who were randomly selected to be interviewed. Data collection included test of understanding the concept in essay form which was previously validated. Based on the results of students’ answers, 20 students have been able to connect between mathematics problems with the learned mathematics topic, the density topic in physics with the volume cube topic, and the question problems with everyday issues. However, it was also found that some students answered the questions with different procedures.